CORRELATION BETWEEN CREATIVE THINKING, OPEN-MINDEDNESS AND INTEREST IN TVET PROGRAM: AN EMPIRICAL STUDY OF SECONDARY SCHOOL STUDENTS IN RIVER STATE, NIGERIA - Imaobong Sunday, Bassey (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
The integration of the TVET program into Nigeria's educational ecosystem reflects the government's commitment to ensuring that students acquire vocational and technical skills for self-development and economic growth. However, indications suggest a declining number of students enrolling in TVET programs. The present study investigated secondary school students' interest in the TVET program based on creative thinking and open-mindedness. Two hundred and three secondary school students from public and private schools in River State, Nigeria, participated in the study. There were 87 (25.6%) responders were 15 years old, 103 (58.0%) were 16 years old, and 13 (12.4%) were 17 years old. There were 119 (59.0%) females and 84 (41.0 percent) males among the responders). They completed self-report measures on interest in TVET, creative thinking assessment, and actively open-minded thinking scale. The findings revealed that creative thinking (? = .183, p < .001) and open-mindedness (? = 168, p< .001) were significant predictors of student interest in TVET among secondary school students in River State. The two predictor variables explained 42.2% of the total variance in the students' interest in TVET. The findings and practical implications of the study are discussed.